2014
DOI: 10.1111/bjdp.12052
|View full text |Cite
|
Sign up to set email alerts
|

Children's utilization of emotion expectancies in moral decision‐making

Abstract: This study investigated the relevance of emotion expectancies for children's moral decision-making. The sample included 131 participants from three different grade levels (M = 8.39 years, SD = 2.45, range 4.58-12.42). Participants were presented a set of scenarios that described various emotional outcomes of (im)moral actions and asked to decide what they would do if they were in the protagonists' shoes. Overall, it was found that the anticipation of moral emotions predicted an increased likelihood of moral ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
9
2
Order By: Relevance
“…In contrast to Hertz and Krettenauer (2014), the current study showed that even young children could predict behaviors within modified experimental procedures that brought out the children's abilities. In Study 1, similar to Hertz and Krettenauer (2014), participants were asked to predict each behavior that was parallelly presented.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to Hertz and Krettenauer (2014), the current study showed that even young children could predict behaviors within modified experimental procedures that brought out the children's abilities. In Study 1, similar to Hertz and Krettenauer (2014), participants were asked to predict each behavior that was parallelly presented.…”
Section: Discussioncontrasting
confidence: 99%
“…Can children predict moral behaviors based on emotions? Krettenauer and his colleagues investigated this possibility (Hertz & Krettenauer, 2014; Krettenauer et al, 2011) and systematically examined the effects of emotions on future moral behaviors of children and adolescents. The results indicated that participants gave more credit to the emotional aspects of judgments about behaviors with age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, regret and sadness experienced by 6-to 7-year-olds about a choice made on one day were associated with making a better choice the following day (O'Connor, McCormack, Beck, & Feeney, 2015). In another example, 4-to 12year-old children indicated being more likely to engage in a costly prosocial act when given reason to expect a positive emotion (pride) as compared with a negative emotion (sadness; Hertz & Krettenauer, 2014).…”
Section: The Present Researchmentioning
confidence: 99%
“…Hertz and T. Krettenauer (2014) researched into the effect of emotions on children's moral choices and found out that the anticipation of moral emotions predicted an increased likelihood of moral choices in antisocial and prosocial contexts. In younger children, anticipated moral emotions predicted moral choice for prosocial actions, but not for antisocial actions.…”
Section: Literature Reviewmentioning
confidence: 99%